2016
DOI: 10.1002/ppul.23531
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of extravascular lung water by ultrasound after congenital cardiac surgery

Abstract: Our results show that lung ultrasound in assessment of postoperative EVLW predicted length of mechanical ventilation and stay in the PICU, and it had less interobserver variability than CXR. Accordingly, lung ultrasound may complement CXR in assessment of lung edema after surgery for congenital heart defect. Pediatr Pulmonol. 2017;52:345-352. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Neonates with congenital heart defects predisposing to pulmonary overflow have a higher B-line count than babies without overflow 78 and the B-line score also correlates with the duration of ventilation. 79 Similar applications could be proposed to evaluate pulmonary overflow in the case of haemodynamically significant patent ductus arteriosus or to guide fluid management albeit specific studies are currently lacking.…”
Section: Broncho-pulmonary Dysplasiamentioning
confidence: 99%
“…Neonates with congenital heart defects predisposing to pulmonary overflow have a higher B-line count than babies without overflow 78 and the B-line score also correlates with the duration of ventilation. 79 Similar applications could be proposed to evaluate pulmonary overflow in the case of haemodynamically significant patent ductus arteriosus or to guide fluid management albeit specific studies are currently lacking.…”
Section: Broncho-pulmonary Dysplasiamentioning
confidence: 99%
“…(Ann Thorac Surg 2020;109:178-84) Ó 2020 by The Society of Thoracic Surgeons L ung ultrasound (LUS) is a noninvasive, easy, and fast technique for the evaluation of pulmonary disease in children, especially in the acute setting. [1][2][3][4][5][6][7][8] Pulmonary complications are common with pediatric cardiac surgery and have been evaluated primarily with chest roentgenograms. [4][5][6][7] Recent studies have evaluated the utility of LUS in children undergoing congenital heart surgery.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Pulmonary complications are common with pediatric cardiac surgery and have been evaluated primarily with chest roentgenograms. [4][5][6][7] Recent studies have evaluated the utility of LUS in children undergoing congenital heart surgery. [4][5][6][7] These studies have shown diagnostic accuracy of LUS for pulmonary complications after surgery including pleural effusion, atelectasis, pneumothorax, and pneumonia.…”
mentioning
confidence: 99%
See 2 more Smart Citations